Beyond Moral Panic: Negotiation Theory and the University Strikes in Nigeria - Isaac Olawale Albert (Journal of Global Initiatives, 2015)
“Moral panic” is a concept of growing importance in the social sciences. It has to do with the emotional reaction of the media, the public, and agents of social control to an emerging or anticipated social problem. My paper uses this concept to portray how Nigerians react to the incessant industrial action by members of the Academic Staff Union of Universities (ASUU) since the 1990s. During these many strikes, which often last for months, Nigerian universities and private businesses domiciled in them are shut down. Members of the public often cast the Academic Staff Union of Universities (ASUU)/Federal Government (FG) face-offs in moral mode and find it easier to blame ASUU more than the government for keeping students out of the classroom. This paper argues that moral panics are now part of the problem rather than a solution. It explains why ASUU suspended its past strikes prematurely without achieving its goal, only to return to same issues shortly after. This “popular outcry against ASUU” explains why the government takes too long to consider the union’s demands for improving the funding of Nigerian universities. Taking the foregoing into consideration, the paper locates a more scientific explanation of the problems in the contexts of (i) obvious poor funding of Nigerian universities as evident in decayed infrastructure and low morale of staff; (ii) government’s lack of capacity to negotiate altruistically with ASUU; (iii) government’s reluctance to implement agreements reached with the university teachers; and (iv) lack of a vibrant civil society in Nigeria that is deeply concerned with the conditions of Nigerian universities. Some recommendations are made on how to solve the problem.